Investigating the Band Alignment of Zn(O, S) with Kesterite (Cu2ZnSnS4) Material for Photovoltaic Application - Margi Jani; Dhyey Raval; Abhijit Ray (Журнал нано- та електронної фізики)
This paper reports theoretical simulation of the band alignment of zinc oxysulfide Zn(O,S) with kesterite (Cu2ZnSnS4) material for the photovoltaic application. Zinc oxysulfide Zn(O,S) is selected for this study due to the possibility of band gap tailoring and non-toxicity. It is widely explored as a buffer layer for the fabrication of CZTS thin film solar cells. A detailed study is presented in order to investigate the consequences of band bending due to the use of Zn(O,S) as a buffer layer in Cu2ZnSnS4 (CZTS) solar cells and corresponding electrical performance is explored using one-dimensional simulation tool SCAPS. Presented analysis shows that the band-gap can be optimized through sulfur content variation, which is beneficial to reduce the band offset with the heterojunction partner material (i.e. CZTS). The optimization is done by monitoring the electrical performance of CZTS solar cells. The open circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF) and efficiency (η) are found to vary in the range of 414 to 417 mV, 26.3 to 26.9 mA/cm2, 21 % to 26 % and 2.3 to 2.8 % respectively with respect to variation in sulfur content in the range of 0 to 30 %.